The Role of Competitive and Cooperative Norms in the Development of Deviant Evaluations. Issue 6 (20th May 2018) - McGuire, Luke; Rizzo, Michael T.; Killen, Melanie; Rutland, Adam
Abstract : The present study examined how peer group norms influence children's evaluations of deviant ingroup members. Following the manipulation of competitive or cooperative norms, participants (children, M age = 8.69; adolescents, M age = 13.81; adults, M age = 20.89; n = 263) evaluated deviant ingroup members from their own and the group's perspective. Children rated cooperative deviancy positively and believed their group would do the same. Adolescents and adults believed that their group would negatively evaluate cooperative deviancy when their group supported a competitive allocation strategy. Reasoning varied based on norm and participants' agreement with deviancy. Understanding an ingroup may not be favorable toward a cooperative deviant in a competitive context is a developmental challenge requiring the coordination of social and moral norms.